Discovery of highly selective κ-opioid receptor agonists: 10α-Hydroxy TRK-820 derivatives. Issue 16 (15th August 2017) - Suzuki, Shinya; Sugawara, Yuji; Tsuji, Riichiro; Tanimura, Ryuji; Kaneko, Chihiro; Yuzawa, Natsumi; Yagi, Mai; Kawai, Koji
Graphical abstract: Abstract: κ-Opioid receptor agonists with high selectivity over the μ-opioid receptor are attractive targets in the development of drugs for pain and pruritus. We previously reported the synthesis of 10α-hydroxy TRK-820 (1 ). In this study, we elucidated the biological properties of1 and optimized its 6-acyl unit by modifying our synthetic route. Among the 10α-hydroxy TRK-820 derivatives prepared, 26 showed the most potent κ-opioid agonist activity (EC50  = 0.00466 nM) and excellent selectivity and22 was the most κ-selective agonist.